The Influence of Financial Literacy on the Consumptive Behavior of Students in the Management Study Program, Faculty of Business and Economics, Islamic University of Indonesia - Sherina Arin Salsabila; Sri Mulyati (Fakultas Ekonomi & Bisnis Universitas Muslim Indonesia, 2023)
This research aims to determine the effect of financial literacy on consumptive behavior in students of the Management Study Program, Faculty of Business and Economics, Islamic University of Indonesia. The sampling technique used was probability sampling with the criteria being students of the Management Study Program at the Islamic University of Indonesia who had taken financial management courses so that a sample of 180 respondents was obtained. This research is quantitative research and uses primary data obtained directly from respondents through questionnaires and processed using the multiple linear regression analysis method. The results of this research indicate that there is a significant negative influence on investment and risk management variables on consumptive behavior. Meanwhile, there is no significant influence on the variables of basic personal financial knowledge and savings on consumptive behavior.